Lumbar Cystic Intradural Schwannoma: A Case Report - Narmer Azzam (Egyptian Spine Association, 2014)
Background Data: Intradural lumbar cystic schwannomas are very rare entity and only about 10 case reports have been reported in the literature. The diagnosis and management remains a challenge for clinical physicians. Purpose: Our objective in presenting this particular case is to highlight the atypical radiological features of intradural spinal schwannoma and how to deal with it surgically and follow up. Study Design: case report. Material and Methods: A case of cystic intradural lesion in a previously healthy 29 years old male is reported. Low back pain and lately right sciatica were the only symptoms. After pre-operative evaluation and preparation, this patient was operated on prone position under general anesthesia. Results: Although the lesion originates from nerve tissue, only 50% of cases have a direct relation with the nerve. Hence complete excision without sacrificing nerve roots is usually feasible and is curative in most cases as in our case. The patient recovered totally intact without any motor, sensory or sphincteric disturbance. The postoperative histological picture of cystic schwannoma, which was not in the preoperative list of differential diagnoses, is discussed. Conclusion: A successful surgical outcome depends on early diagnosis [before neurological damage has occurred], meticulous investigation [on any intractable nonspecific low back pain], and complete excision. (2014ESJ066)